DOLMEN'S DECORATION PATTERNS IN SUMBA, INDONESIA - Haris Sukendar (Berkala Arkeologi, 1987)
In this article, An Introduction to a Unique Culture of Sumba, HB. Mude assumed that the first settlers of Sumba came by boat from Malaka, Singapore, Riau, Java, Bali, Sima, Rote and Sabu, under the leadership of Umbu Mandoku and his wife, Rambu Humba. To honour his wife, the island was named Humba or Sumba. Sumba consists of West and East Regency. The climate is relatively hot with short rainy season and prolonged dry period. Sumba is a typical karst region, and bordered by the alluvial plain of Melolo areas, from where the river Melolo now flows eastward.